Model of a 5-MA Linear-Transformer-Driver Accelerator: Comparison of MITL Performance for Bremsstrahlung Electron Beam Diodes and Z-Pinch Loads. (31st January 2023) - Gong, Zhenzhou; Wei, Hao; Fan, Siyuan; Yao, Weibo; Wu, Hanyu; Qiu, Aici
Abstract : A transmission line circuit model was conducted to compare the performances of the two-level 2.5 Ω magnetically insulated transmission lines (MITLs) system of a 5-MA linear-transformer-driver (LTD) accelerator for two kinds of typical loads, including bremsstrahlung electron beam diodes and Z-pinch loads. Both the electron current loss in the pulse front during the magnetic insulation setup process and the electron flow distribution in the magnetic insulation steady state were analyzed. When the accelerator drives an electron beam diode load with impedance of 1.20 Ω (a single level), the duration of the magnetic insulation setup is about 12 ns, the current loss is about 130 kA in a single MITL level, the maximum electron flow current is about 50 kA in the end of MITL, and its amplitude decreases gradually after the steady magnetic insulation is established. When the accelerator drives a Z-pinch load with length of 1.5 cm, radius of 1.2 cm, and mass of 0.3 mg/cm, the duration of the magnetic insulation setup is almost zero, the maximum electron flow current in the end of MITL can reach about 55 kA (a single level), and the waveform of the electron flow resembles a saddle shape, which reaches the peak at the pinch stagnation time.